Preoperative hydronephrosis predicts advanced bladder cancer but is not an independent factor for cancer-specific survival after radical cystectomy - Höfner, Thomas; Haferkamp, Axel; Knapp, Lena; Pahernik, Sascha; Hadaschik, Boris; Djakovic, Nenad; Wagener, Nina; Hohenfellner, Markus (Urologia internationalis, 2011)
Introduction: Hydronephrosis and BMI are analyzed together with established factors such as TNM stage and surgical margins in a multivariate modality to investigate their status as independent prognostic factors for bladder cancer-specific survival in patients undergoing radical cystectomy. Patients and Methods: We studied a prospective cohort of 328 patients who underwent radical cystectomy for bladder cancer at our institution. Statistical analyses were performed using the Kaplan-Meier method, Kendall-tau rank correlation and multivariate Cox proportional hazard model. Results: Hydronephrosis was positively correlated with advanced tumor stage, positive lymph node involvement and positive surgical margins. Adjusted for all other investigated parameters, BMI and hydronephrosis did not affect cancer-specific survival. In multivariate analysis only non-organ-confined disease (HR: 1.40, 95% CI: 1.04-1.87, p = 0.024), positive lymph node stage (HR 1.71: 95% CI: 1.12-2.61, p = 0.013) and positive surgical margins (HR 3.00, 95% CI: 1.74-5.15, p < 0.001) were prognostic factors. Conclusions: Hydronephrosis at the time of radical cystectomy is significantly correlated with the presence of more advanced bladder cancer and positive surgical margins. However, the long-established parameters pT stage, pN stage and surgical margins predominantly influence cancer-specific survival for patients undergoing radical cystectomy irrespective of hydronephrosis and BMI status.
Published online: November 2, 2010
Gesehen am 29.06.2022